PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V SDN 21 TEMBAN - Nur Haeni; Umiyati Jabri; Saleha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the low learning outcomes of fifth grade students in Science at SDN 21 Temban. The purpose of this study was to improve student learning outcomes in Science through the application of the Teams Games Tournament (TGT) Cooperative Learning Model. The type of research used was Classroom Action Research (CAR) conducted in two cycles. This study used the Kammis and Mc. Taggart model, which consists of four stages: planning, implementation, observation, and reflection. The subjects of this study were 18 fifth-grade students at SDN 21 Temban, comprising 12 boys and 6 girls. Data collection techniques included observation, testing, and documentation. The results showed that the implementation of the Teams Games Tournament (TGT) cooperative learning model improved learning outcomes. This was evident in the increase in the percentage of students participating in the pre-action phase from 28% to 56% in Cycle I, and to 89% in Cycle II. Therefore, it can be concluded that the implementation of the Teams Games Tournament (TGT) cooperative learning model improved the science learning outcomes of fifth-grade students at SDN 21 Temban.